Dream of Polio Free Pakistan - when will it become a reality? - Reetika Yadav; Roopa Hariprasad; S. Nandhini; S. Vallikavitha (University of New South Wales, 2023)
Pakistan is one of the two endemic countries for polio, reporting co-circulation of WPV1 and cVDPV2. Pakistan is classified by the International Health Regulations (IHR) as a state infected with Wild Poliovirus type 1 (WPV1) and circulating Vaccine derived poliovirus type 2 (cVDPV2) with potential risk of international spread. We describe an ongoing outbreak of WPV1 in North Waziristan district of southern Khyber Pakhtunkhwa (KP) province in Pakistan and the last documented outbreak of cVDPV2. The first case of the WPV1 outbreak was documented in the month of April 2022, after more than a year of polio free status. Since then, 20 cases in total have been reported, of which 87 percent had never received OPV through essential immunization. Major reasons which might be responsible for Pakistan's failure in the eradication of polio including governance issues, lack of health facilities, low routine immunization, or refusal of immunization, security threat to immunization staff, extensive public movement, and presence of polio reservoirs/zones in border regions with Afghanistan. Pakistan's struggle against polio eradication was further fuelled by the COVID-19 pandemic which brought a standstill to the routine immunizations. The threat to the Global Polio Eradication stems from reintroduction of the poliovirus and emergence of circulating vaccine derived poliovirus (cVDPV) in the polio-free countries. Hence, control of the WPV1 and cVDPV2 transmission in Pakistan is an international concern.